Undergraduate and Postgraduate Programmes in Remote Sensing at Universiti Teknologi Malaysia - Mohd , Mohd Ibrahim Seeni; Hashim, Mazlan (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1997)
The Faculty of Geoinformation Science amd Engineering at universiti Teknologi Malaysia has been offering BSc programmes in land surveying and property management since 1972 However, with the increasing needs for professionals in other fields such as remote sensing, geoinformatic and land administration & development, the faculty now offers three more new courses, manely (I) B.Se (Remote Sensing). (2) B ~c (Ueointormutics, (3) B,Sc (Land Administration & Development) The Faculty also has been offering postgraduate programmes related to geomatic engineering, remote sensing, geoinformatics, GPS surveying, hydrography, property management and land administration & development. This paper presents an overview of the undergraduate and postgraduate programmes in remote sensing at the faculty.